Composite Materials Properties as Influenced by Phase Geometry - Nielsen, Lauge Fuglsang (Springer Berlin Heidelberg : Imprint: Springer, 2005)
This book deals with the mechanical and physical behavior of composites as influenced by composite geometry. This monograph provides a comprehensive introduction for researchers and students to modern composite materials research with a special emphasis on the influence of geometry to materials properties. Composite Materials enables the reader to a better understanding of the behavior of natural composites, improvement of such materials, and design of new materials with prescribed properties. A number of examples are considered in the book: Special composite properties considered are stiffness, shrinkage, hygro-thermal behavior, viscoelastic behavior, and internal stress states. Other physical properties considered are thermal and electrical conductivities, diffusion coefficients, dielectric constants and magnetic permeability. Special attention is given to the effect of pore shape on the mechanical and physical behavior of porous materials.